Wood coating dust emission in the Malaysian furniture industry: a case study - Ratnasingam, Jegatheswaran; Hj Arshad, Tajuddin; Khoo, Albert; Ab Latib, Hazirah; Lim, Choon Liat; Ayenkaren, Jegathesan; Lee, Yan Yi; Mariapan, Manohar (North Carolina State University, 2020)
The objectives of this study were to evaluate the current dust extraction efficiency used in the Malaysian furniture industry and also the effectiveness of using engineered nanoparticle (ENP)-added coatings to reduce dust emission in the wood finishing operation. This study was in response to the enforcement of the Clean Air Regulation (2014), which requires significant improvements in the air quality and the work environment in the wood-based industry in Malaysia. A series of sanding experiments with different abrasive grit sizes and different coating types were conducted to determine the dust emission levels. The results suggested that higher capture velocity of 30 m/s was necessary to effectively capture the wood coating dust emitted. Further, ENP-added wood coatings did not differ markedly from conventional coatings with regard to dust emission characteristics. The study also revealed that total dust concentration had an inverse relationship, while the amount of finer dust particles was linearly related to the coating film hardness. Therefore, to comply with the Clean Air Regulation, the Malaysian furniture industry needs to significantly improve its dust extraction system.